OP028 Single cell RNA sequencing of t-cells in Crohn's disease identifies tissue specific drug targets. (16th January 2018) - Festen, E; Weersma, R; Uniken Venema, W T; Voskuil, M D; Graham, D
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory disease, predominantly affecting the terminal ileum. 1 Genome-wide association studies have identified 200 CD risk loci. 2 These loci are enriched for genes involved in T cell signalling, highlighting their importance in CD pathology. 3 To get true insight in the underlying pathomechanisms, it is crucial to study these T cells in their disease-relevant context: the intestinal mucosa. 4 We performed single cell RNA sequencing (scRNA-seq) of paired mucosal and blood T cell samples from CD patients, aiming to increase our insight in CD pathomechanisms and to identify novel drug targets. Methods: We performed scRNA-seq of 5292 CD3+ T cells isolated from peripheral blood (PBL) and from ileal biopsies of CD patients. Biopsies were dissociated and separated into T cells from epithelium (IEL) and lamina propria (LPL). ScRNA-seq was performed with an adapted SmartSeq2 protocol, using 3′-end library generation, and unique molecular identifiers. Results: Unsupervised clustering of our scRNA-seq data identified five distinct T-cell types. The distribution of cell types differs between IEL, LPL and PBL: cytotoxic T cells (CTL) dominate the IEL, the blood T cell reservoir is mainly composed of quiescent T cells, and T-helper 17 (Th17) cells are the largest population in the LPL. Th17 cells and CTLs show the highest proportion of differentially expressed CD risk genes: such as CD69 and FOS in Th17 cells, and CX3CR and NKG7 in CTLs. Aligning potential IBD drug targets5 to CTL specific genes, we find that Etrolizumab, but not Vedolizumab, specifically appears to target mucosal CTLs. Two potential drug repositioning opportunities targeting mucosal Th17 cells, are MSX-122, an anti-tumour CXCR4-antagonist, and Rivenprost, which targets PTGER4, and is being tested in a phase II trial in UC (Figure 1). Conclusions: We have conducted a unique disease- and tissue-specific transcriptomic characterisation of T cells in CD. We have profiled five distinct T-cell types using scRNAseq data. We show that CD risk genes are significantly overexpressed in ileal mucosal Th17 and CTLs, and provide promising targets for future therapies in CD patients.